2018
DOI: 10.1126/scitranslmed.aah3924
|View full text |Cite
|
Sign up to set email alerts
|

A human-derived antibody targets misfolded SOD1 and ameliorates motor symptoms in mouse models of amyotrophic lateral sclerosis

Abstract: Mutations in the gene encoding superoxide dismutase 1 (SOD1) lead to misfolding and aggregation of SOD1 and cause familial amyotrophic lateral sclerosis (FALS). However, the implications of wild-type SOD1 misfolding in sporadic forms of ALS (SALS) remain unclear. By screening human memory B cells from a large cohort of healthy elderly subjects, we generated a recombinant human monoclonal antibody (α-miSOD1) that selectively bound to misfolded SOD1, but not to physiological SOD1 dimers. On postmortem spinal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 54 publications
2
64
0
1
Order By: Relevance
“…40 Researchers from Neurimmune (Schlieren, Switzerland) recently reported the development of a fully human antibody against amyotrophic lateral sclerosis targeting pathologically misfolded SOD1, α-miSOD1, from a memory B-cell library from healthy elderly individuals. 41 Phase III trials involving aducanumab, a bona fide human antibody with potent β-amyloid clearing capabilities, were stopped prematurely. 42 In previous works, we found that anti-PrP C antibodies can efficaciously counteract prions, 6 a finding later confirmed by several other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…40 Researchers from Neurimmune (Schlieren, Switzerland) recently reported the development of a fully human antibody against amyotrophic lateral sclerosis targeting pathologically misfolded SOD1, α-miSOD1, from a memory B-cell library from healthy elderly individuals. 41 Phase III trials involving aducanumab, a bona fide human antibody with potent β-amyloid clearing capabilities, were stopped prematurely. 42 In previous works, we found that anti-PrP C antibodies can efficaciously counteract prions, 6 a finding later confirmed by several other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, repeated tests of the same mouse is feasible, which enables longitudinal studies of drug efficacy with a powerful statistical design in which individual subjects are compared to themselves over time. Therapies that target patients with mutations of the SOD1 gene have successfully completed early clinical study phases, and have prolonged survival in SOD1 related animal models 27,28 . Microendoscopy measurements in animal models given these drugs should be performed to understand the effects of the drug on motor unit distribution over time in individuals, and further validate the measurement method.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Misfolded protein aggregates, including some containing SOD1, are a well-described feature of ALS (27)(28)(29). One research group used a computer modeling program to predict that resveratrol would reduce SOD1 protein aggregates (30).…”
Section: Protein Aggregationmentioning
confidence: 99%